Pigmented scleredema: An unusual presentation - Yogindher singh (Journal of Pakistan Association of Dermatologists, 2024)
Scleredema adultorum (SA) of Buschke is a rare disorder of idiopathic etiology. Clinically differentiated by diffuse, symmetric, and non-pitting induration of the skin which typically affects the neck, shoulders, trunk, arms, face, and, in rare cases, the buttocks and thighs. Here, we describe a case with scleredema diabeticorum with an uncommonly pigmented appearance.